Posttraumatic stress following childbirth: psychometric properties of the Brazilian version of the City Birth Trauma Scale - Flavia de Lima Osório; Ana Carolina Rossini Darwin; Eduardo Antonio Bombonetti; Susan Ayers (Taylor & Francis Group, 2022)
Objective To seek validity and reliability evidence of the Brazilian version of the City Birth Trauma Scale (BiTS-Br) and establish diagnostic accuracy. Method A total of 343 mothers (up to one year after childbirth, 30.8 years old on average) completed the BiTs-Br and other instruments screening for posttraumatic stress disorder (PTSD), depression, and anxiety for convergent validity analysis. Structural validity was verified using exploratory techniques (principal components analysis), while discriminant validity was checked using the known-groups method and ROC curve. The Structured Clinical Interview for DSM-5 was applied via telephone interviews. Test-retest reliability was obtained in a 15-30-d interval. Results A two-factor structure was found (birth-related and general symptoms), with excellent test-retest reliability (0.73) and internal consistency (0.91). Moderate/strong associations (>0.62) were found with correlated symptoms and posttraumatic stress. The scale had a diagnostic accuracy of 86.7% and a cutoff point >28 was the most appropriate, with a sensitivity of 72% and specificity of 83%. Conclusions BiTS-Br presented excellent psychometric indexes, similar to the original version and other cross-culturally adapted versions. Thus, it can be widely used in scientific research and clinical settings to support the identification and treatment of PTSD.